Tularemie, "kniha" druhá - Macela, A (Epidemiologie, mikrobiologie, imunologie, 1998)
As a continuation of Libich's monograph (Tularemie. Prague, Avicenum 1981) the author presents findings assembled in experiments pertaining to postinfectious immunity on a model of intracellular infection with the microorganism Francisella tularensis.
Keywords: buněčná imunita; Antibodies, Bacterial; Tularemia; protilátky bakteriální; Francisella tularensis; Animals; Humans; lidé; Immunity, Cellular; zvířata; tularemie